Afforestation With Different Tree Species Causes a Divergent Evolution of Soil Profiles and Properties - Morazzo, German; Riestra, Diego Rene; Leizica, Emmanuel; Álvarez, Lucila; Noellemeyer, Elke (Frontiers in Forests and Global Change, 2021)
Land-use change affects soil morphology, chemistry, biology, and nutrient regimes. Numerous studies have documented that in land-use conversions from agricultural land to forest, or from plantations to restored natural savanna most soil attributes and functions change. The purpose of the present study was to evaluate the changes brought about by afforestation of degraded croplands and to understand the impact of forest vegetation on soil evolution in a semiarid region where soils originally co-evolved with a savanna biotope. We used long-term experiments (> 40 years) of five tree species: Pinus halepensis (PH), Pinus halepensis inoculated with ecto-mycorrhiza at planting (PM), Pinus pinea (PP), Eucalyptus spp. (E), and Gleditsia triacanthos (G) and compared these to an agricultural soil (A) at the same site near Santa Rosa, La Pampa in the semiarid center of Argentina. Soil profiles were described, and samples taken for chemical and physical analyses of soil properties [organic matter (OM), pH, cation exchange capacity (CEC) and exchangeable cations, particle size distribution (texture), aggregate stability (MWD), bulk density (BD), porosity (TP), and water holding capacity (WHC)]. We found a strong effect of tree species on soil profile morphology and on all studied variables. PM and G had highest OM, CEC, neutral pH, higher TP, WHC, while PH, PP, and E had acid pH, lower base saturation, OM, TP, and WHC. The effect of tree species on the soil profile was noticeable to the depth of about 40 cm comprising the A and AC horizons but not the C horizon. The results showed that to obtain reasonable results of OM sequestration under forest systems, tree species should be chosen to include legumes to improve C/N stoichiometry for C fixation, or inoculation with mycorrhiza to promote microbial transformation of forest litter.